'Skanky stories': Breaking boundaries of sexual taboo in women's travel narratives. Issue 9 (1st September 2020) - Falconer, Emily
Abstract: This paper argues that women travelers engage with and subsequently re-tell stories of taboo sexual encounters as part of a wider discourse in securing cultural capital through independent, global travel and adventure. Using data from my research Emotion and embodiment in the experiences of independent women tourists (2009-2012), I give examples of sexual etiquette in travelling discourse by re-positioning the 'shocking' boundaries of sexual taboo through travel stories, analysing the performances of 'pleasure-seeking' discourses of third-wave feminist sexuality, and moving discussion beyond this to explore white privilege and fetishising the 'Other'. Many women's travel stories display a heightened heterosexuality that radically differs from some feminist concerns that female sexualisation is geared towards the fantasy male gaze (Pritchard and Morgan 2000 ) and these stories are integrated into her travelling journey of exploration, experience, stimulus, whilst providing some entertaining 'fodder'. Of further note is how these pleasure-seeking discourses tie into adventure narratives so prominent in backpacking literature; that of 'rough', 'dirty' and 'skanky' immersive experiences. The narratives of women travelers as they re-tell stories of sexual behavior throughout their travels reflect the desires for extreme experiences to enhance their stories. The language and sexual vocabulary of the women as they discuss sexual identity whilst travelling play with racial privilege, and cross the boundaries of classed, gendered and cosmopolitan 'respectability' in a conscious manner.